Vocational education and training for the common good : the macrosocial benefits of VET - (:unkn) unknown (Publications Office of the European Union, 2011)
"VET might be expected to offer macrosocial benefits through two mechanisms: the aggregate human capital stock and education equity. The VET impact on macrosocial benefits was tested using a new VET dataset (1960-90, at higher and secondary level) for 21 OECD countries, building on Green et al. (2006). Using regression analysis, we explore whether aggregate levels of VET influence a range of macrosocial benefits: health, rights and social order. The analysis is not conclusive but future research directions are highlighted. Although increasing the share of VET in education does not lead directly to macrosocial benefits, it could still affect them through its impacts on equity. Increasing the level of secondary academic qualifications could be harmful for educational equity, while investing in VET at secondary and higher level is equity neutral. We investigated, through literature review, ways to change institutional VET arrangements for educational equity. General lessons drawn from five case studies illustrate how policy interventions in VET may benefit educational equity" (Hrsg., BIBB-Doku)
Keywords: S 4.3.3 Effizienz & Effektivität des Berufsbildungswesens; S 4.3.5 Bildungsbeteiligung & soziale Gerechtigkeit; S 4.3.6 Human Capital; I 2.2 Europa; Berufsbildung; Kosten-Nutzen-Analyse; Makroökonomie; Soziale Indikatoren; Soziale Stabilität; Bildungschancengleichheit; Humankapital; Europa